Cross-sectional and longitudinal equivalence scales for West Germany based on subjective data on life satisfaction: Paper presented at the fifth meeting of the Society for the Study of Economic Inequality (ECINEQ) Bari (Italy), 22th - 24th July 2013 - Jürgen Faik (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The present study calculates variable, cross-sectional as well as longitudinal equivalence scales on the basis of the German 1984-2010 Socio-Economic Panel (SOEP) database for West Germany. It follows the individual variant for calculating subjective equivalence scales using life satisfaction as a proxy variable for utility. The cross-sectional scale estimates are characterized by relatively low scale values which is typical for the subjective scale approach. As a further main result, the estimated longitudinal equivalence scales reveal some but rather slight cohort-specific scale differences. Especially, the unsatisfactory fit of the paper's regressions points to the need for more research activities in this strand of social science research. The latter must be emphasized since equivalence scales are very important for social policy. Specifically, this holds true for longitudinal scales in order to capture cohort effects and, thus, to deal with intra- and intergenerational aspects of well-being (and corresponding differences).
Keywords: D30; D31; D60; 330; equivalence scales; life satisfaction; longitudinal analysis; cohorts' well-being